Implementation of General Principles of Good Governance in State Administrative Law in Indonesia - Suaib, Rahmatia Nasution; Doholio, Aiga; Nupura, Moh. Naharudin (Administratie: Jurnal Administrasi Publik, 2025)
The General Principles of Good Governance (AUPB) are of significant urgency in the Indonesian state system because they function as a normative foundation to ensure the implementation of clean, transparent, accountable governance per the principles of democracy and law. This study aims to analyze the application of AUPB in the practice of state administrative law in Indonesia while identifying the challenges in its implementation. The research method used is a literature study with a normative approach, through the analysis of various rules and regulations, legal doctrines, scientific literature, and court decisions related to the application of AUPB, to provide a comprehensive picture of the position of this principle in government practice. The study results indicate that AUPB has obtained legal legitimacy through various regulations, especially Law Number 30 of 2014 concerning State Administration. However, its implementation in the field still faces quite complex obstacles, both from the structural aspect in the form of weak oversight mechanisms and enforcement of sanctions, as well as from the cultural aspect in the form of low understanding and commitment of the bureaucratic apparatus to the basic principles of AUPB. This situation is reflected in the ongoing high number of state administrative disputes resulting from violations of these principles. The impact of this research emphasizes the need for strengthened regulations, increased civil servant capacity, and a consistent instillation of a legal culture so that the implementation of the AUPB can truly realize good governance and increase public trust in state institutions.